2017
DOI: 10.2298/gensr1702677w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glu-1 and glu-3 allelic variations on wheat glutenin macropolymer (GMP) content as revealed by size-exclusion high performance liquid chromatography (SE-HPLC)

Abstract: 2017): Effects of glu-1 and glu-3 allelic variations on wheat glutenin macropolymer (GMP) content as revealed by size-exclusion high performance liquid chromatography vol 49, no. 2,(677)(678)(679)(680)(681)(682)(683)(684)(685)(686)(687)(688)(689)(690)(691) Gluten macropolymers (GMPs), formed by seed storage proteins glutenins and gliadins through intermolecular disulfide bond, confer dough viscoelasticity and wheat processing quality. Glutenins consist of high and low molecular weight glutenin subunits (HMW-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Namely, comparing with the composition of high molecular weight glutenin subunits (HMW-GS) in CB037B at the Glu-1 locus (1Ax1, 1Bx17 + 1By18, 1Dx5 + 1Dy10), CB037A had the composition of 1Ax1, 1Bx17 + 1By18, 1Dx2 + 1Dy10 at this locus; CB037C had the same HMW-GS composition at Glu-1 to CB037B. For the composition of low molecular weight glutenin subunits (LMW-GS) at the Glu-3 locus, CB037B and CB037A had Glu-A3c, Glu-B3h, and Glu-D3a subunits, whereas CB037C only had the Glu-A3c and Glu-D3a subunits and missed Glu-B3h subunit (Wang et al 2016;Wu et al 2017). Recently, the original CB037 was identi ed to be genetically heterogeneous for resistance to wheat stripe rust, and the Pst-resistant line CB037-PstR and Pst-susceptible line CB037-PstS were isolated; the CB037-PstR carried a single dominant resistance gene, which was a 1BL/1RS translocation line and likely carried Yr9 (Zheng et al 2020).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Namely, comparing with the composition of high molecular weight glutenin subunits (HMW-GS) in CB037B at the Glu-1 locus (1Ax1, 1Bx17 + 1By18, 1Dx5 + 1Dy10), CB037A had the composition of 1Ax1, 1Bx17 + 1By18, 1Dx2 + 1Dy10 at this locus; CB037C had the same HMW-GS composition at Glu-1 to CB037B. For the composition of low molecular weight glutenin subunits (LMW-GS) at the Glu-3 locus, CB037B and CB037A had Glu-A3c, Glu-B3h, and Glu-D3a subunits, whereas CB037C only had the Glu-A3c and Glu-D3a subunits and missed Glu-B3h subunit (Wang et al 2016;Wu et al 2017). Recently, the original CB037 was identi ed to be genetically heterogeneous for resistance to wheat stripe rust, and the Pst-resistant line CB037-PstR and Pst-susceptible line CB037-PstS were isolated; the CB037-PstR carried a single dominant resistance gene, which was a 1BL/1RS translocation line and likely carried Yr9 (Zheng et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Among the newly identi ed wheat genotypes for wheat tissue culture and genetic transformation, CB037 showed the special features of a model genotype including short plant height, early maturity, high tissue culture response from three explants (anthers, immature embryos, and mature embryos), and strong resistance to powdery mildew (PM) (Tao et However, the original CB037 is a mixed population. Three near isogenic lines (NILs) of CB037A, CB037B, and CB037C were identi ed in the original CB037 according to the glutenin composition (Wang et al 2016;Wu et al 2017). Namely, comparing with the composition of high molecular weight glutenin subunits (HMW-GS) in CB037B at the Glu-1 locus (1Ax1, 1Bx17 + 1By18, 1Dx5 + 1Dy10), CB037A had the composition of 1Ax1, 1Bx17 + 1By18, 1Dx2 + 1Dy10 at this locus; CB037C had the same HMW-GS composition at Glu-1 to CB037B.…”
Section: Introductionmentioning
confidence: 99%
“…It is also crucial for disulfide bond formation. The number of free sulfhydryl groups determines the formation of high molecular weight glutenin subunits (HMW-GS), low molecular weight glutenin subunits (LMW-GS), and the glutenin macropolymers (GMP) [ 5 , 6 , 7 ]. The study of Yoshino et al [ 8 ] confirmed that the amount of disulfide bonds in flour also dropped along with the quantity of sulfur in wheat grains, which in turn affected the viscosity of flour.…”
Section: Introductionmentioning
confidence: 99%
“…Glutenins consist of high and low molecular weight glutenin subunits (HMW-GS and LMW-GS) accounting for about 40% of wheat storage proteins, and their composition and content are important factors affecting flour processing quality. LMW-GS account for 60% of glutenins and serve as important components of the gluten macropolymers (GMPs) that confer dough viscoelasticity (WRIGLEY et al, 1996;YAN et al, 2009;RASHEED et al, 2014;WU et al, 2017).…”
mentioning
confidence: 99%
“…Considerable work has shown that the allelic variations at both Glu-1 and Glu-3 loci are closely related to dough strength and breadmaking quality. In particular, some glutenin subunits and alleles have shown a positive effect on dough properties and processing quality such as 1Dx5+1Dy10 encoded by Glu-D1d (PAYNE, 1987;WU et al, 2017), 1Bx17+1By18 encoded by Glu-B1i (GUO et al, 2019), Glu-A3a (ZHEN et al, 2014) and Glu-B3h (WANG et al 2016). However, in addition to a few of HMW-GS, fewer superior genes at Glu-3 loci in bread wheat have been identified and cloned.…”
mentioning
confidence: 99%